"Jantan" as a Positive Symbol in Tenas Effendy's Ungkapan Melayu According to S. Othman Kelantan's Malay Criticism Framework: (Simbol "Jantan Positif" dalam Ungkapan Melayu Tenas Effendy dari Gagasan Kritikan Melayu S. Othman Kelantan) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
This paper discusses about the symbol of "jantan" (male dominance) which have positive meanings, found in Malay proverbs by Tenas Effendy. This discussion uses the Framework of Malay Critiques by S. Othman Kelantan, which contains 10 principles. The underlying meanings in the "jantan" symbol will be analyzed to scrutinize the worldview of those who conceptualize these Malay proverbs as well as their association with the negative traits of male dominance. Malay proverbs that have been examined will be able to illuminate the inherent thought patterns of the Malay society, and at the same time, explore their vast knowledge of the world. Research on the Malay "Jantan" is important to analyze the lens in which was viewed by a predominantly oral society, as well as the explicit and implicit meanings of the symbols in Malay proverbs.Keywords: Symbol, male, proverbs, underlying meaning, Malay critiques